The effect of gender and male distinctiveness threat on prejudice against homosexuals - Figueiredo, Camilla Vieira de (2020)
Positive distinctiveness threat is central for understanding ingroup bias, but its role in gender differences in the expression of sexual prejudice is not yet satisfactorily elucidated. We analyzed this issue by proposing that sexual prejudice is a defensive strategy to ensure intergroup distinctiveness and that consequently, heterosexual men are more prejudiced against homosexuals than heterosexual women because they strive more for positive distinctiveness. In Study 1 (N = 232), we manipulated the target of prejudice (gay men vs. lesbians) and found that men exhibited more prejudice against gay men, while women did not significantly differentiate their prejudice against these target groups. In Study 2, we manipulated the target group of prejudice (gay men vs. lesbians) in a sample of men (N = 79) and confirmed that they made greater efforts to differentiate heterosexual men from gay than heterosexual women from lesbians. In Study 3 (N = 178), we indirectly manipulated the threat to the distinctiveness between homosexual and heterosexual and demonstrated that the need for positive distinctiveness mediates the relationship between gender and prejudice in men but not in women. Finally, in Study 4 (N = 75), we directly manipulated the perception of distinctiveness for men and women and measured sexual prejudice by means of an implicit measure (IAT). The results showed more implicit prejudice in men than in women when intergroup distinctiveness was threatened. Our results have important implications for understanding sexual prejudice by shedding light on the role played by the distinctiveness threat of gender difference in expressing homophobia.